Analisis Perumusan dan Implementasi Kebijakan Pengelolaan Pasar dalam Penataan Pasar Pagi di Pasar Sentral Pinrang - N. Nurhayati; B. Barisan; Muh Akbar Ali Darlis; Ahmad Mustanir (Public Inspiration : Jurnal Administrasi Publik, 2026)
This study aims to analyze the formulation and implementation of local government policies in regulating the existence of morning markets around the Central Market of Pinrang. This research employs a qualitative approach, with data collected through interviews, observations, and documentation. Data analysis is conducted descriptively using the public policy analysis framework of William N. Dunn and the policy implementation model of Van Meter and Van Horn.The findings indicate that, normatively, market management policies already have a strong legal basis through Regional Regulation of Pinrang Regency Number 6 of 2024, supported by Regent Regulation Number 24 of 2016. However, the policy formulation process remains suboptimal, particularly in the stages of problem definition and forecasting, which have not fully considered the socio-economic conditions of traders.Furthermore, policy implementation has not been effective, as reflected in persistent violations, limited market facilities, weak coordination among agencies, and inconsistent supervision. Traders tend to continue operating outside the designated market area due to more strategic and profitable locations. This study concludes that the main issues lie not only in policy implementation but also in weaknesses in the policy formulation process. Therefore, improvements are needed in both aspects to produce policies that are more adaptive, responsive, and effective in addressing real conditions in the field.